A Note of the Collection of Ceropegia ensifolia Bedd. (Apocynaceae:Ceropegieae) from Nilgiris, Southern Western Ghats, India - Jeevith, Selvaraj; Rajasekar, Chinnaiyan; Samydurai, Ponnusamy; Kunhikannan, Cheravengat (Indian Forester, 2019)
No Abstract.